Imitatio Christi and the Gospel Genre - Capes, David B. (Bulletin for biblical research, 2003)
This article considers that the Gospel genre belongs to the category of ancient biography designed to provide the reader and hearer with a pattern to imitate. The literary and cultural ethos of the formative period of early Christianity prepared the first disciples to "imitate Christ" whenever the Gospels were liturgically read. In fact, the ethical instructions "walk as he walked," "imitate Christ," or even "follow me" required a narrative definition. So the imitatio Christi provided a significant impulse for the writing of the Gospels, and concomitantly, the Gospels provided the narrative definition for what it meant to follow Jesus.